Longitudinal Survey of Astrovirus infection in different bat species in Zimbabwe: Evidence of high genetic Astrovirus diversity - Chidoti, Vimbiso; De Nys, Hélène; Abdi, Malika; Mashura, Getrude; Pinarello, Valérie; Chiweshe, Ngoni; Matope, Gift; Guerrini, Laure; Pfukenyi, Davies; Cappelle, Julien; Mwandiringana, Ellen; Missé, Dorothée; et al. (Peer Community Journal)

(untitled)
Astroviruses (AstVs) have been discovered in over 80 animal species including diverse bat species and avian species. A study on Astrovirus circulation and diversity in different insectivorous and frugivorous chiropteran species roosting in trees, caves and building basements was carried out at 11 different sites across Zimbabwe. Pooled and individual faecal sampling methods were used for this study, with collection dates ranging from June 2016 to July 2021. In two sites, Magweto and Chirundu, sampling was carried out at monthly intervals from August 2020 to July 2021. Astroviruses and bat mitochondrial genes were amplified using pan-AstVs and CytB /12S RNA PCR systems respectively. Phylogenetic analysis of the RdRp Astrovirus sequences revealed a high genetic diversity of astroviruses. All the bat astroviruses tested in this study clustered with the Mamastrovirus genus. Two distinct groups of amplified sequences were identified. One group was comprised of sequences isolated from Hipposideros, Rhinolophus and Eidolon helvum spp. clustered with Human Astrovirus strains: HuAstV types1-6, HuAstV-MLB1-3 and HuAstV-VA-1. The second group comprising the majority of the sequences clustered with different strains of Bat AstVs. Results from the longitudinal study at Magweto and Chirundu showed an overall AstV prevalence of 13.7% and 10.4% respectively. Peaks of AstV infection at Chirundu coincided with the period when juveniles are 4-6 months old. By combining data from our previous work on Coronaviruses, we also anaylzed co-infection of bats with Coronaviruses and Astroviruses at Magweto and Chirundu sites for which the prevalence of co-infection was 2.6% and 3.5% respectively.